2023
DOI: 10.3390/medicina59030468
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Transition Shock, Professional Stressors, and Intent to Leave the Nursing Profession during the COVID-19 Pandemic

Abstract: Background and Objectives: Moving nurses to a COVID-19 department may cause the phenomenon of transition shock, which occurs when already employed nurses change jobs. A set of confusing and uncertain feelings arise due to the unfamiliar work environment, which may lead to their intention to leave the nursing profession. The aim of this study was to examine transition shock and the contribution of both the respondents’ characteristics and the presence of stressors to the occurrence of transition shock in nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It was also observed that during the COVID-19 pandemic, the intention of nurses to leave the profession increased by about 5% more compared to the period before the COVID-19 pandemic [27]. Such results are caused, among other things, by an increase in the level of transition shock [28], [29]. The higher average values recorded in the relationships factor possibly indicate that newly employed nurses during their 1…”
Section: Discussionmentioning
confidence: 94%
“…It was also observed that during the COVID-19 pandemic, the intention of nurses to leave the profession increased by about 5% more compared to the period before the COVID-19 pandemic [27]. Such results are caused, among other things, by an increase in the level of transition shock [28], [29]. The higher average values recorded in the relationships factor possibly indicate that newly employed nurses during their 1…”
Section: Discussionmentioning
confidence: 94%